A smart parcel locker system with parcel status and image notifications via LINE application - Chaiyong Soemphol; Chonlatee Photong; Piyapat Panmuang (Bulletin of Electrical Engineering and Informatics, 2026)
During the COVID-19 pandemic, online shopping grew rapidly, leading to more parcel deliveries. However, recipients are not always home to receive them. Some existing systems send alerts via SMS or email, but these methods often incur additional costs. To address this issue, we developed a smart parcel box. It uses IoT and solar power to work efficiently and sustainably, and it sends free delivery alerts through the LINE notify app, which is popular in Thailand. The prototype was tested using four parcel sizes: CD-sized (15×15×15 cm), 0+4 (17×11×10 cm), 2A (14×20×12 cm), and M-sized (27×43×20 cm). Results showed that the 0+4 parcel size had the fastest average detection and notification time of 8.42 s, followed by CD sized (9.81 s), 2A (9.9 s), and M-sized parcels (10.1 s). The M-sized parcel had the lowest standard deviation (SD) (0.42 s), while 0+4 was the least consistent (1.718 s). Differences in detection times were due to parcel size and placement but did not affect notifications. The system achieved 100% detection across all sizes, and the images allowed users to verify parcel details and sender information. These results demonstrate that the prototype is reliable, energy-efficient, and suitable for further development and adaptation in smart delivery systems.